2020
DOI: 10.37506/ijfmt.v14i3.10695
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Moringa oleifera Seed Oil Extract on Insulin Level in Alloxan-Induced Diabetic Rat (Rattus norvegicus)

Abstract: Moringa oleifera is a plant that can be used and grown intensively in several Southeast Asian countries. This study aims to determine the effect of Moringa oleifera seed oil extract on the levels of the insulin and blood glucose levels of Rattus norvegicus induced by alloxan. This study used 30 female Wistar white rats induced by alloxan. Rats were divided into 6 groups. Groups 3 to 6 were injected 100, 200, 300, 400 mg/kg BW extract of Moringa oleifera seed oil, respectively. Group 1 neither had alloxan induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The results of the present study indicate that the leaf and seed extracts of M. oleifera have a reducing effect on glucose levels (i.e., antihyperglycemic or antidiabetic) in alloxaninduced diabetic mice. Therefore, this result confirms the antihyperglycemic properties of M. oleifera as previously reported by several researchers [58,89,105,108]. Many studies have reported the positive effects of herbal medicines in the management of diabetes owing to their content of bioactive phytochemicals that are frequently implicated as having an antidiabetic effect [132,133].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study indicate that the leaf and seed extracts of M. oleifera have a reducing effect on glucose levels (i.e., antihyperglycemic or antidiabetic) in alloxaninduced diabetic mice. Therefore, this result confirms the antihyperglycemic properties of M. oleifera as previously reported by several researchers [58,89,105,108]. Many studies have reported the positive effects of herbal medicines in the management of diabetes owing to their content of bioactive phytochemicals that are frequently implicated as having an antidiabetic effect [132,133].…”
supporting
confidence: 90%
“…12 Oxidative Medicine and Cellular Longevity treat diabetes [84][85][86][87]. Numerous studies have reported the antidiabetic (hypoglycemic) properties of M. oleifera leaf extract [88][89][90][91][92][93][94][95][96][97][98][99], seed extract [100][101][102][103][104][105][106][107][108], root extract [109,110], pod extract [57,111], fruit extract [19,112], and flower extract [113,114]. The hypoglycemic effect of the leaf, seed, root, pod, fruit, and flower of M. oleifera extracts was variable in the experimental animal models of induced diabetes, according to the dose and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%